Robotic allied with the STEAM Methodology as a proposal to solve the challenges of Professional Education during the Covid-19 pandemic - Nascimento, Jean Mendes (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2020)
The educational environment undergoes constant changes and the teaching methodologies must be updated according to their contexts and in their due times of performance, outdated methodologies end up not being effective if applied in new generations. In the face of the world pandemic scenario presented in 2020, a model of remote classes was adopted following rules of social distance. This article seeks to present an alternative for the formation of students' skills in a technical school in the city of São Paulo. For this, the STEAM methodology is used to develop projects on an online platform based on real simulations of the daily life of the area. At the end, a positive result is presented for the methods approached according to the evaluation of the students participating in the project.